Th e eff ect of Providing Food Made from Resistant Starch Fiber (Dioscorea Esculenta, Maranta Arundinaceae L, Cucurbita Moschata, Manihot Utilissma) on the Improvement of Glycated Albumin in Type 2 Diabetes Mellitus Patients at Dr. Sardjito General Hospital - Dwita Dyah Adyarini; Hemi Sinorita; Muhammad Robikhul Ikhsan (Acta Interna The Journal of Internal Medicine, 2019)
Background. One of the characteristics of the Diabetes diet is giving food with a high complex carbohydrates, particularly fiber.  The benefit of resistant starch fiber includes maintaining blood glucose and increasing insulin sensitivity.Aims. This study aimed to find the effect of providing food made from resistant starch fiber (Dioscorea esculenta, Maranta arundinaceae L, Cucurbita moschata, Manihot utilissma) on the improvement of blood glucose control in diabetes patients based on glycated albumin test.Methods. The Quasi-experimental study was used in diabetes type-2 patients who visited endocrinology polyclinic at Dr Sardjito Hospital, during 1 November 2015-31 January 2016. Food made from the resistant starch fiber was served as a daily snack for one month. Blood glycated albumin was examined before and after food providence. SPSS was used for statistical analyses.Results.  We recruited 17 subjects in the control group and 17 subjects in the treatment group. In the control group, the index of albumin was significantly deteriorated from 15.1% to 18.13%. In the treatment group, the index of albumin was reduced from 29.71% to 18.73% showing an improvement of 10.97% (p= 0.01).Conclusion. There was a significant improvement of blood glycated albumin (10.97%) after consuming food that was made from resistant to starch fiber (p=0.01).